Physiological responses and swimming technique during upper limb critical stroke rate training in competitive swimmers - Funai, Y.; Matsunami, M.; Taba, S. (Journal of Human Kinetics, 2019)
The aim of this study was to examine how arm stroke swimming with critical stroke rate (CSR) control would influence physiological responses and stroke variables in an effort to identify a new swimming training method. Seven well-trained male competitive swimmers (19.9 ± 1.4 years of age) performed maximal 200 and 400 m front crawl swims to determine the CSR and critical swimming velocity (CV), respectively. Thereafter, they were instructed to perform tests with 4 × 400 m swimming bouts at the CSR and CV. The swimming time (CSR test: 278.96 ± 2.70 to 280.87 ± 2.57 s, CV test: 276.17 ± 3.36 to 277.06 ± 3.64 s), heart rate, and rated perceived exertion did not differ significantly between tests for all bouts. Blood lactate concentration after the fourth bout was significantly lower in the CSR test than in the CV test (3.16 ± 1.43 vs. 3.77 ± 1.52 mmol/l, p < 0.05). The stroke rate and stroke length remained stable across bouts in the CSR test, whereas the stroke rate increased with decreased stroke length across bouts in the CV test (p < 0.05). There were significant differences in the stroke rate (39.27 ± 1.22 vs. 41.47 ± 1.22 cycles/min, p < 0.05) and stroke length (2.20 ± 0.07 vs. 2.10 ± 0.04 m/stroke, p < 0.05) between the CSR and CV tests in the fourth bout. These results indicate that the CSR could provide the optimal intensity for improving aerobic capacity during arm stroke swimming, and it may also help stabilize stroke technique. Key words: arm stroke swimming; stroke rate; stroke length; aerobic performance; swimming training.